IMPROVING THE LANGUAGE SKILLS OF 3-4 YEAR OLD CHILDREN THROUGH THE APPLICATION OF SENSORY BOX MEDIA AT THE ANGGREK TEGALSONO KINDERGARTEN - Umi Atiyah; Agustiarini Eka Dheasari (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to improve the language skills of children aged 3–4 years through the application of sensory box media at the Anggrek Tegalsono Kindergarten. The problem faced in the learning process is the low ability of children to recognize, pronounce, and understand everyday vocabulary. This study uses a classroom action research (CAR) approach implemented in two cycles, with each cycle including the planning stage, action implementation, observation, and reflection. The research subjects consisted of 10 children from a playgroup aged 3–4 years. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results showed that the application of sensory box media can significantly improve children's language skills. Children become more active in speaking, able to name objects, and use simple sentences in everyday communication. Play activities through sensory box media help children connect concrete experiences with language skills. Thus, sensory box media is proven effective in developing the language skills of early childhood at the Anggrek Tegalsono Kindergarten